PENGARUH EKSTRAK AIR KULIT BUAH PISANG AMBON (Musa paradisiaca L.) PADA MODEL HEWAN RESISTENSI INSULIN - Elis Susilawati; Nita Selifiana; Sinta Paramudita Supriana (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
Ambon banana (Musa paradisiaca L.) is one kind of banana that its peel has activities as antioxidant. It can control glucose level of blood and preventing complications in diabetes mellitus. This research was aiming to evaluate the effect of banana peel water extract in the decreased blood glucose levels and determining the effective dose in increasing the value of KTTI. This research was done by using animal as a model for insulin resistance, that was induced by lipofundin and fructose oraly during 28 days. Animal’s used were 30 male mice swiss Webster. It was divided into six groups, that were negative control, positive control, standard drug group of Metformin 65 mg/Kg bw, banana peel water extract with the dose 100 mg/Kg bw, 200 mg/Kg bw and 400 mg/Kg bw. The parameter was blood glucose level and KTTI by giving insulin 0,0125U/Kg bw intraperioteneally. The result showed that banana peel water extract with the dose 400 mg/Kg bw was the effective dose with the value of KTTI 1,16.